2019
DOI: 10.1038/s41598-019-51427-y
|View full text |Cite
|
Sign up to set email alerts
|

Self-DNA release and STING-dependent sensing drives inflammation to cigarette smoke in mice

Abstract: Cigarette smoke exposure is a leading cause of chronic obstructive pulmonary disease (COPD), a major health issue characterized by airway inflammation with fibrosis and emphysema. Here we demonstrate that acute exposure to cigarette smoke causes respiratory barrier damage with the release of self-dsDNA in mice. This triggers the DNA sensor cGAS (cyclic GMP-AMP synthase) and stimulator of interferon genes (STING), driving type I interferon (IFN I) dependent lung inflammation, which are attenuated in cGAS, STING… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 51 publications
0
55
0
Order By: Relevance
“…42 Additionally, acute exposure to cigarette smoke also causes airway inflammation with fibrosis and emphysema of mice in a STING-dependent manner. 43 Our recent study proposed that STING may drive NLRP3 inflammasome-mediated pyroptosis and cellular injury in sepsis-induced cardiac injury. 20 During liver ischemia and reperfusion, STING suppression of macrophages inhibited the overactivation of NLRP3 inflammasome and excessive secretion of IL-1β and IL-18, eventually reducing liver injury.…”
Section: Discussionmentioning
confidence: 99%
“…42 Additionally, acute exposure to cigarette smoke also causes airway inflammation with fibrosis and emphysema of mice in a STING-dependent manner. 43 Our recent study proposed that STING may drive NLRP3 inflammasome-mediated pyroptosis and cellular injury in sepsis-induced cardiac injury. 20 During liver ischemia and reperfusion, STING suppression of macrophages inhibited the overactivation of NLRP3 inflammasome and excessive secretion of IL-1β and IL-18, eventually reducing liver injury.…”
Section: Discussionmentioning
confidence: 99%
“…This self-DNA activates the cGAS-STING pathway, triggering type I IFN-dependent lung inflammation, which is attenuated in cGAS, STING or type I IFN receptor-deficient mice. 120 Further investigation of whether the cGAS-STING pathway is also involved in self-DNA sensing and pathogenesis in COPD patients may lead to therapeutic targets.…”
Section: Chronic Obstructive Pulmonary Diseasementioning
confidence: 99%
“…100 In addition, cGAS-STING activation by self-DNA release upon cigarette smoke exposure leads to type I interferon-dependent lung inflammation. 120 Recently, Han et al reported that airway epithelial cGAS is critical for the induction of allergic airway inflammation in mice. 134 Altogether, these findings indicate cGAS-STING activation is a critical driver of lung inflammation.…”
Section: Lung Inflammation and Fibrosismentioning
confidence: 99%
“…Cigarette smoke is well described as injurious to pulmonary barrier function primarily due to epithelial cell injury and concurrent release of self-DNA and activation of the cGAS/STING pathway. 131 Downstream interferon signaling and neutrophilic infiltrates then contribute to tobacco smoke-related fibrosis and emphysematous changes, with IFNAR1-antibody acting to inhibit phenotypes in exposed mice. Complicating the story, another group has uncovered that STING is actually decreased in settings of cigarette-exposure-mediated DNA damage and release, resulting in worsened emphysema, though—again—a compensatory effect cannot be ruled out.…”
Section: Exposures and Therapymentioning
confidence: 99%